2015
DOI: 10.1080/23766808.2015.1052230
|View full text |Cite
|
Sign up to set email alerts
|

Phytoseiid mites (Acari: Phytoseiidae) in the northern coastal region of the Rio Grande do Sul State, Brazil

Abstract: This work aims to evaluate the phytoseiid fauna in natural environments of the coastal plain of the northern coast of the Rio Grande do Sul State, Brazil. The plants were sampled from locations within the counties of Tramandaí and Osório during the last month of each season. Three locations were chosen in the Tramandaí area: (A1) -sand dunes; (A2) -mangrove and (A3) -forest plantation; and one in Osório: (A4) -hill with dense rainforest. A total of 561 specimens belonging to 29 species were collected. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In Pantanal, Mendonça et al (2019) found 35 phytoseiid species on 40 native plants and Rodrigues et al (2020) found 11 phytoseiid species associated with Myrtaceae plants in the Caatinga. In the Brazilian Atlantic Forest, Ferla and Moraes (2002) found 23 phytoseiid species on 45 plant species; Castro and Moraes (2010) found 54 phytoseiid species on 187 species of plants; Demite et al (2013) found 31 Phytoseiid species on two native plants in fragments of semideciduous seasonal forest; Rocha et al (2015) reported 29 Phytoseiid species on 62…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Pantanal, Mendonça et al (2019) found 35 phytoseiid species on 40 native plants and Rodrigues et al (2020) found 11 phytoseiid species associated with Myrtaceae plants in the Caatinga. In the Brazilian Atlantic Forest, Ferla and Moraes (2002) found 23 phytoseiid species on 45 plant species; Castro and Moraes (2010) found 54 phytoseiid species on 187 species of plants; Demite et al (2013) found 31 Phytoseiid species on two native plants in fragments of semideciduous seasonal forest; Rocha et al (2015) reported 29 Phytoseiid species on 62…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Z. malvinae, which is related to Grassland, it is distributed throughout Brazil and occurs in rubber trees, vineyards, citrus, and coffee crops (Matioli et al 2002; De Vis et al 2006; Mineiro et al 2006; Diehl et al 2012. Typhlodromalus aripo was more associated with Grazing and Grazing Exclusions, this species was also associated to unstable environments with extreme windy conditions (Rocha et al 2015).…”
Section: Amblyseius Tamatavensismentioning
confidence: 90%
See 1 more Smart Citation
“…In material collected from A. ntundu from Cameroon and DR Congo the ratio was 3.1: 1 (Moraes et al 2006). In the case of A. manihoti, a species frequently collected in South America, the s4: Z1 ratio ranged from 1.8: 1 (Rocha et al 2015) to 4.1: 1 (Guanilo et al 2008, Demite et al 2017. In this way, the s4 / Z1 ration seems to be an unstable character and, therefore, would not be the best character to separate two genera.…”
Section: Remarksmentioning
confidence: 97%
“…Measurements of the holotype of N. tunus were provided by Moraes et al (2000), whereas complementary descriptions were provided from populations of the French Caribbean islands (Moraes et al, 2000), Argentina (Guanilo et al, 2008a), Brazil (Lofego et al, 2004;Ferla et al, 2011;Gonçalves et al, 2013;Rocha et al, 2015) and Peru (McMurtry and Moraes, 1989;Guanilo et al, 2008b). Due to the great similarity between N. tunus and N. neotunus, the possible synonymy between them was mentioned in the literature (Moraes and Mesa, 1988;Lofego, 1998).…”
Section: Introductionmentioning
confidence: 99%